Nomenclator botanicus for Appendicularia DC. (Melastomataceae, Marcetieae) - Silva, Diego Nunes Da; Rocha, Maria José Reis Da; Guimarães, Paulo José Fernandes (Phytotaxa, 2020)
Appendicularia is a neotropical genus of annual herbs, currently with four accepted species after a recent inclusion of three species that were formerly placed in Ernestia. However, during nomenclatural studies on Marcetieae, we observed that the combination A. rubra was mistaken, since its basionym Ernestia rubra belongs to the clade “Ernestia incertae sedis”. Here we exclude A. rubra from the genus, reinstating it to Ernestia, and consequently recognizing Appendicularia with three species. The type collections and nomenclatural comments are provided, as well as lectotypifications for A. thymifolia and E. rubra. Finally, Brachypremna has been listed as a synonym under Ernestia by previous treatments, but is synonymized here under Appendicularia.